An experimental comparative study between polypropylene and laminated lower limb prosthetic socket - Jweeg, Muhsin J.; Radhi, Samira K.; Neama, Haider F. (Al-Khwarizmi Engineering Journal, 2007)
Most researchers concentrate their studies on the design, stress and pressure distributions of the prosthetic socket. A little attention is considered for the stiffness of the various materials of the prosthetic sockets. Prosthetic laminated sockets in Iraq are costly to be manufactured while polypropylene socket is relatively cheap in comparing with the laminates. Experimental study is conducted to compare the stiffness of five prosthetic sockets made of different materials. Compression, three point flexural and tensile tests are implemented by the Testometric machine. The laminate sockets give better results in compression than polypropylene. Polypropylene gives good results in bending compared with the laminate sockets. When the socket loads are mainly in compression i.e. the low activity level patients, it seems that any of the tested sockets could be used, however, when the load will be not only in compression but in flexion as well i.e. high activity patients, socket No.1 and 5 could be used.